2021
DOI: 10.1007/s40122-021-00307-3
|View full text |Cite
|
Sign up to set email alerts
|

Restorative Neurostimulation for Chronic Mechanical Low Back Pain: Results from a Prospective Multi-centre Longitudinal Cohort

Abstract: Introduction: Low back pain impacts most people throughout the course of their lives and contributes significantly to the global burden of disease. In some patients, symptoms resolve with little intervention, while others are amenable to surgical intervention, some cases are intractable to current care paradigms. Restorative neurostimulation is an emerging therapy for chronic mechanical low back pain. Methods: We conducted a prospective postmarket follow-up of 42 patients treated for longstanding chronic mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Subjects also reported clinically significant reductions in patient-centric outcomes of disability (ODI), pain interference (BPI-9), and PGIC. Thomson et al, 2021 538 Post-market prospective clinical follow-up 42 I-B NRS, ODI, EQ-5D-5L Among the 37 patients completing 2-year follow-up, NRS pain scores improved from 7.0 ± to 3.5 ± 0.3, ODI scores improved from 46.2 ± 2.2 to 29.2 ± 3.1, and health-related quality of life improved from 0.426 ± 0.035 to 0.675 ± 0.030. Additionally, 57% of patients experienced a greater than 50% reduction in pain, and 51% of patients benefited by a greater than 15-point reduction in ODI, both substantial improvements.…”
Section: Neuromodulationmentioning
confidence: 99%
“…Subjects also reported clinically significant reductions in patient-centric outcomes of disability (ODI), pain interference (BPI-9), and PGIC. Thomson et al, 2021 538 Post-market prospective clinical follow-up 42 I-B NRS, ODI, EQ-5D-5L Among the 37 patients completing 2-year follow-up, NRS pain scores improved from 7.0 ± to 3.5 ± 0.3, ODI scores improved from 46.2 ± 2.2 to 29.2 ± 3.1, and health-related quality of life improved from 0.426 ± 0.035 to 0.675 ± 0.030. Additionally, 57% of patients experienced a greater than 50% reduction in pain, and 51% of patients benefited by a greater than 15-point reduction in ODI, both substantial improvements.…”
Section: Neuromodulationmentioning
confidence: 99%
“…Percutaneous PNS of the LMBN is a relatively new modality, and to date, there are 10 human, clinical studies focusing on nonspinal neuromodulation for chronic axial LBP (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Kapural et al (25) was the first to publish clinical data using the SPRINT device.…”
Section: Discussionmentioning
confidence: 99%
“…However, deeper analysis of the data shows that though the primary outcome was not significant, the actual values of functional outcome measures were significantly improved at 120 days for the treatment group compared to the sham in ODI (difference −5.4 95% CI −9.5 to −1.2, p = 0.011) and EQ-5D (Difference 0.071 95% CI 0.018 to 0.123, p = 0.009) respectively, though VAS trended toward significance (Difference −0.9, 95% CI −1.6 to −0.1, p = 0.032) ( 19 ). Next, Thomson et al ( 16 ) investigated NRS, ODI, and EQ-5D changes on 37 patients for 2 years. They found that at 2 years all outcome measures had significantly improved from baseline ( p < 0.001) ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The safety profile over the initial 2-year period has been published previously. 15 The late term safety profile contains 1 related event (Table 3). This cohort reports no device related serious adverse events.…”
Section: Safety Outcomesmentioning
confidence: 99%